Development of Mobile and Computer Application Based on Philippine Electrical Code (2017) for Single and Three-Phase Electrical Designing - Jonas Martin; Russel Isaac Kabigting; Glend Jr. Lingad; Nathaniel Magtoto; Cenon Jr. III Yutuc; Louie G. Serrano (Universitas Komputer Indonesia, 2025)
This paper presents a mobile and computer application designed to automate electrical design and load scheduling, strictly complying with the 2017 Philippine Electrical Code (PEC). Developed to assist engineers, electricians, and students, the tool streamlines the planning of single-phase and three-phase systems for both residential and commercial buildings. It features vital computational resources, including voltage drop analysis, load calculation, and safe branch circuit distribution, which are critical for preventing overloads and ensuring energy efficiency. By bridging theoretical engineering principles with practical code compliance, this intuitive application significantly reduces manual calculation errors and enhances overall safety in electrical installations.